Comparative Analysis of Diurnal and Seasonal Variations in Precipitation of Mesoscale Convective System and Non-Mesoscale Convective System over Borneo Island - Azka, Mukhamad Adib; Trilaksono, Nurjanna Joko (Jurnal Meteorologi dan Geofisika, 2024)
Convective storms, which play a critical role in producing severe weather events, are often associated with mesoscale convective systems (MCS). The most favorable tropical regions for MCS development include the Indonesian Maritime Continent (IMC), with Borneo Island being a prominent area. Borneo Island features unique topography and is influenced by the surrounding oceans, resulting in MCS with the largest average size and most extended lifespan compared to other islands within the IMC. Previous studies on MCS focused on occurrence statistics and case studies. However, analyses distinguishing characteristics of MCS and non-MCS precipitation remain limited over the IMC. This study examines the diurnal and seasonal variations and their respective contributions over Borneo Island. MCS identification and tracking were performed using the Flexible Object Tracker (FLEXTRKR) algorithm. The results indicate that MCS precipitation typically occurs from nighttime to early morning, while non-MCS precipitation primarily occurs during the daytime until the evening. Furthermore, MCS precipitation occurs more frequently over the ocean, while non-MCS precipitation is primarily observed over land. Seasonally, MCS precipitation is most prominent during the December–January–February (DJF) season, particularly over the South China Sea, parts of West Kalimantan, Sarawak, Central Kalimantan, and the Java Sea. Conversely, MCS precipitation is less dominant during the June–July–August (JJA) season. The contribution of precipitation produced by MCS exceeds 50% of the total precipitation, whereas non-MCS precipitation contributes approximately 20–40%. The differences in precipitation produced by MCS and non-MCS clouds will affect for soil water content, vulnerability to hydrometeorological disasters, and further understanding of climate and weather.